Cover Image. (19th February 2019) - Ramseier, Christoph A.; Nydegger, Martina; Walter, Clemens; Fischer, Gabriel; Sculean, Anton; Lang, Niklaus P.; Salvi, Giovanni E.
Abstract : The cover image is based on the Article Time between recall visits and residual probing depths predict long‐term stability in patients enrolled in supportive periodontal therapy by Christoph A. Ramseier et al., DOI: 10.1111/jcpe.13041 .